The study of the canonical Watson-Crick DNA base pairs by Moller-Plesset perturbation method: the nature of their stability - Danilov, V.I.; Anisimov, V.M. (Біополімери і клітина, 2004)
Gas-phase gradient optimization was carried out on the canonical Watson-Crick DNA base pairs using the second-order Moller-Plesset (MP2) perturbation method at the 6-31G* and 6-31G*(0.25) basis sets. It is detected that full geometry optimization at the MP2 level leads to an intrinsically nonplanar propeller-twisted and buckled geometry of G-C and A-T base pairs. Morokuma-Kitaura (MK) and reduced variational space (RVS) methods of the decomposition for molecular Hartree-Fock interaction energies were used for the investigation of the hydrogen bonding in the Watson-Crick base pairs in question. It is shown that the stability of the hydrogen-bonded DNA base pairs originates mainly from electrostatic interactions. At the same time the polarization, charge transfer and dispersion interactions also make considerable contribution to the attraction energy of bases. Використовуючи теорію збурень Моллера-Плессета у другому порядку, проведено градієнтну оптимізацію канонічних уотсон-криківських пар основ у базисах 6-31G* і 6-31G*(0,25). Знайдено, що повна оптимізація геометрії на рівні МР2 спричинює внутрішньо неплоску пропелер-повернуту і вигнуту геометрію пар основ G-C і А-Т. Для дослідження водневих зв'язків в уотсон-криківських парах використано методи Мороку ми-Кітаури та зменшеного варіаційного простору для розкладу хартрі-фоківської енергії молекулярної взаємодії. Показано, що стабільність водневих зв'язків пар основ переважно з'являється за рахунок електростатичної взаємодії. В той же час поляризаційна і исперсійна компоненти та взаємодія з перенесенням заряду також роблять значний внесок в енергію притяжіння основ. Используя теорию возмущений Моллера-Плессета во втором порядке, проведена градиентная оптимизация канонических уотсон-криковских пар оснований в базисах 6-31G* и 6-31G* (0,25). Обнаружено, что полная оптимизация геометрии на уровне МР2 приводит к внутренне неплоской пропеллер-повернутой и изогнутой геометрии пар оснований G-C и А-Т. Для исследования водородных связей в уотсон-криковских парах оснований использованы методы Морокумы-Китауры и уменьшенного вариационного пространства для разложения хартри-фоковской энергии молекулярного взаимодействия. Показано, что стабильность водородно-связанных пар оснований возникает, как правило, благодаря электростатическим взаимодействиям. В то же время поляризационная и дисперсионная компоненты, а также взаимодействие с переносом заряда в свою очередь вносят значительный вклад в энергию притяжения оснований.